4CPS-070 The clinical pharmacist: an essential actor in times of crisis. Issue 1 (23rd March 2023) - Rhaymi, C; Chaibi, A
Abstract : Background and Importance: During the health emergency period related to the emergence of the COVID-19 pandemic, clinical pharmacists have played a vital role in mitigating medication errors, especially prescription errors in hospitals. Aim and Objectives: The aim of this study was to carry out a descriptive analysis of the pharmaceutical interventions (PI) on the prescriptions of the patients of the COVID units of our establishment. Material and Methods: A prospective study was conducted on patients with positive COVID-19 status admitted to a hospital COVID unit over a period of four months. The pharmaceutical analysis prompted interventions to rectify medication-related errors. Results: The study included 108 patients. Prescription analysis led to 63 PIs. The sex ratio (M/F) was 0.5 in a favour of female predominance. Hypertension was the most common cardiovascular disease, affecting 34% of patients. Most drug-related problems were overdose accounting for 38% (16/63). The most common PI in 40% of cases was dosage adjustment (18/63). The main drug classes concerned were general anti-infective agents for systemic use 25% (16/63), followed by corticosteroids 23% (15/63) and hydroxychloroquine 19% (12/63) especially in the event of interaction with drugs that lengthen the QT interval. Conclusion and Relevance: The commitment of clinical pharmacy in such a pandemic is therefore important. Its presence has led to a reduction in the problems of drug prescriptions. References and/or Acknowledgements: 1. No conflict of interest. Conflict of Interest: No conflict of interest